Impact of Feeding on Contaminated Prey on the Life Parameters of Nesidiocoris Tenuis (Hemiptera: Miridae) Adults. Issue 1 (30th September 2016) - Wanumen, Andrea Carolina; Sánchez-Ramos, Ismael; Viñuela, Elisa; Medina, Pilar; Adán, Ángeles
Abstract: Insecticide selectivity to natural enemies is an important concern in integrated pest management programs. Although there is a wide range of information concerning pesticide lethal and sublethal effects on contaminated surfaces, little is known when the route of exposure occurs at a trophic level. This study evaluates this route of pesticide intake on the omnivorous predator Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) for the first time. Under laboratory conditions, prey treated with six insecticides (flubendiamide, spirotetramat, deltamethrin, flonicamid, metaflumizone, and sulfoxaflor) were offered to N. tenuis adults for 3 days. Mortality (24, 48, and 72 h after treatment), offspring production (third until eighth day) and longevity were documented. Metaflumizone and sulfoxaflor were classified as moderately harmful products because although the percentage of mortality was only 28 and 36%, respectively, both products caused a severe decrease in offspring production and longevity. Flonicamid and flubendiamide were classified as slightly harmful products; although they did not have a lethal effect, sublethal impact was important on the parameters studied. Spirotetramat and deltamethrin were insecticides categorized as harmless. This information could be useful for selecting the most appropriate insecticides to control pests in tomato crops in which N. tenuis is a relevant biological control agent.